152 To characterise the nature of neonatal cytopenia in an infant presenting with a CDC42 mutation and NOCARH – neonatal-onset cytopenia with dyshaematopoiesis, autoinflammation, rash, and hemophagocytosis. (17th August 2022) - Drury, Ruth; Cheesebrough, Beth; Craze, Janet; Qureshi, Amrana; Anand, Geetha; Douglas, Andrew
Abstract : Aims: To characterise the nature of neonatal cytopenia in an infant presenting with a CDC42 mutation and NOCARH – neonatal-onset cytopenia with dyshaematopoiesis, autoinflammation, rash, and hemophagocytosis. This condition has been described in only nine patients globally. Methods: An 8-week-old girl presented with multiple episodes of anaemia, thrombocytopenia and intermittent neutropenia. These episodes coincided with an elevated CRP and multiple infections, including viral respiratory tract infections, bacterial conjunctivitis, a urinary tract infection and possible osteomyelitis of the tibia. She required six blood transfusions and six platelet transfusions by eight weeks old. Platelet transfusion increments were minimal unless preceded by intravenous immunoglobulin (IVIG) at least 48-hours prior to transfusion. She also had failure to thrive, a persistent oxygen requirement due to recurrent aspiration severe abdominal distension secondary to delayed bowel opening, gastro-oesophageal reflux, and fixed left talipes. Results: At eight weeks, she had a haemoglobin of 61 g/L, platelets 8x109/L, white cell count 5.71x109/L, neutrophils 1.31x109/L, lymphocytes 3.17x109/L, reticulocytes 0.035x1012/L, Prothrombin time 11.5 sec, INR 1.1, APTT 22.3, fibrinogen 4.6, ferritin 1547.2 micrograms/L, LDH 724 IU/L and CRP 257mg/L. Blood film showed red cell anisocytosis, polychromasia, nucleated red blood cells present, thrombocytopenia and occasional plasmacytoid cells, and a few primitive cells seen. Bone marrow aspirate showed an aparticulate and paucicellular sample so no comment could be made about megakaryocytes, with good myeloid and erythroid maturation, erythroid dysplasia and no evidence of haemophagocytosis or blasts. Anti Neutrophil and anti-lymphocyte antibodies were detected. Exome sequencing revealed a de novo mutation in the CDC42 gene, which is associated with NOCARH. Conclusion: The CDC42 gene encodes the cell division control protein 42 homolog protein. This protein is a small GTPase of the rho-subfamily, which are ras-related signalling molecules. CDC42 is important in maintaining hematopoietic stem cell quiescence in the bone marrow and regulates the balance between erythropoiesis and myelopoiesis. NK cell dysfunctions and constitutively elevated expression of IL18 may contribute to the autoinflammatory phenotype seen. CDC42 also activates the transcription factors NFκB and STAT3, which are important in inflammation and leukocyte development and activation. The term 'inflammatory actinopathies' has been suggested in recognition of the link between actin dysregulation and autoinflammation in NOCAHR. Neonatal cytopenia in case reports is poorly defined. Haemophagocytosis occurs outside the neonatal period. We have shown that neonatal cytopenia results from dyserythropoeisis and likely reduced production of white cells and platelets but also that there is a significant autoimmune component, likely from immune dysregulation which is shown by the poor platelet increment and response to IVIG as well as the presence of antineutrophil antibodies which explained the variable neutrophil response from neutropenia to neutrophilia. A possible pathogenesis is a direct effect of CDC42 mutation on hematopoietic progenitor cells, secondary to inflammation-related bone marrow suppression, or due to auto-antibodies against blood cells. This report contributes to the understanding of cytopenia in CDC42 mutations associated with NOCARH and demonstrates a spectrum of disease that does not include haemophagocytic lymphohistiocytosis.